Disparities in the long-term survival of adolescent and young adult diffuse large B cell lymphoma survivors. (December 2021) - Berkman, Amy M.; Andersen, Clark R.; Puthenpura, Vidya; Livingston, J.A.; Ahmed, Sairah; Cuglievan, Branko; Hildebrandt, Michelle A.T.; Roth, Michael E.
Abstract: Purpose: The population of adolescent and young adult (AYA, ages 15–39 years) diffuse large B-cell lymphoma (DLBCL) survivors is growing, however long-term overall survival patterns and disparities are largely unknown. Methods: The current study utilized the Surveillance, Epidemiology, and End Results (SEER) registry to assess the impact of race/ethnicity, sex, socioeconomic status, and rurality on long-term survival in 5-year DLBCL survivors using an accelerated failure time model. Results: Included were 4767 5-year survivors of AYA DLBCL diagnosed between the years 1980 and 2009 with a median follow-up time of 13.4 years. Non-Hispanic Black survivors had significantly worse long-term survival than non-Hispanic White survivors (Survival Time Ratio (STR): 0.53, p < 0.0001). Male sex (STR: 0.57, p < 0.0001) and older age at diagnosis were also associated with reduced long-term survival. There was no evidence that survival disparities improved over time. Conclusions: Racial disparities persist well into survivorship among AYA DLBCL survivors. Studies investigating specific factors associated with survival disparities are urgently needed to better address these disparities. Highlights: Racial disparities in survival persist decades into AYA DLBCL survivorship. Male survivors have worse long-term survival than female survivors. Older age at diagnosis is associated with unfavorable long-term survival. Disparities have not improved over time.